106 MORTALITY FOLLOWING HIP FRACTURE AMONG NURSING HOME RESIDENTS. (25th October 2022) - Crowley, P; Cloney, T; Ahern, E
Abstract: Background: Little is known about mortality following hip fracture among Nursing Home (NH) residents. Prognostic data is important to guide management, including osteoporosis treatment. Methods: We conducted a retrospective cohort study of all patients admitted to an Irish tertiary hospital from NHs with hip fracture during the years 2017-2020 inclusive. Mortality was assessed at 90, 180 and 365 days (one-year) following admission. Results: One patient was lost to follow up, leaving 233 in the analysis group. 147 were female. Mean age was 85. All-cause mortality was 18.03% at 90 days, 27.04% at 180 days and 37.34% at one year. One-Year Mortality (OYM) was 34.01% among females and 43.02% among males. Among those aged 90 or over, OYM was 45.59% (31/68), being 65.22% (15/23) among males and 35.56% (16/45) among females. In those aged 75 or over, OYM was 39.9% (81/203), being 48.57% (34/70) among males and 35.34% (47/133) among females. In those aged under 75, OYM was 20% (6/30). OYM was 42.31% (11/26) among those who could mobilise independently before fracture, 37.23% (51/137) among those requiring an aid, 33.9% (20/59) among those requiring assistance, and 45.45% (5/11) among those unable to mobilise. 62 Rockwood Clinical Frailty Scales (CFS) were recorded (median score 7, range 5-9). OYM was 0% (0/4) for CFS 5, 50% (8/16) for CFS 6, 31.43% (11/35) for CFS 7, 80% (4/5) for CFS 8 and 100% (0/2) for CFS 9. Conclusion: Mortality among NH residents following hip fracture was highest in older males. While mobility before fracture was a poor predictor of mortality, CFS showed promise among a smaller sample size.